Lattice Boltzmann Method simulation of flow and forced convective heat transfer on 3D micro X-ray tomography of metal foam heat sink - Hamidi, E. (Elsevier France-Editions Scientifiques Medicales Elsevier, 2022)
Fluid flow and thermal distribution in isothermal forced convection heat transfer through metal foams are studied. The true geometry of the metal foam samples are obtained by Micro-Computed Tomography (micro-CT) scanning. The Lattice Boltzmann Method (LBM) is used to calculate fluid flow and heat transfer in environments with high geometric complexity. The flow field and the temperature field are solved using the Multi-Relaxation Time (MRT) and Bhatnagar-Gross-Krook (BGK) collision schemes, respectively. The three-dimensional forced convection heat transfer in five metal foam samples with different pore densities (5, 10, 20, 60 and 80 PPI) as well as various porosities (73.69-92.37) in the Reynolds number range of 50-1000 considering two different fluids with Prandtl numbers of 0.7 and 7.0 are analyzed. The correlations between the flow and the heat transfer in metal foam samples are discussed based on numerical results. The results showed that the properties of the foam samples are more responsive to the variations of porosity than the pore density. Conversely, velocity profile and local Nusselt number are directly affected by the pore density. The numerical method developed in this work is able to predict the flow characteristics and heat transfer at the pore scale in the reconstructed geometry of porous structures of real samples.